2005
DOI: 10.1152/ajprenal.00144.2005
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II, reactive oxygen species, and Ca2+signaling in afferent arterioles

Abstract: In afferent arteriolar vascular smooth muscle cells, ANG II induces a rise in cytosolic Ca(2+) ([Ca(2+)](i)) via inositol trisphosphate receptor (IP(3)R) stimulation and by activation of the adenine diphosphate ribose (ADPR) cyclase to form cyclic ADPR, which sensitizes the ryanodine receptor (RyR) to Ca(2+). We hypothesize that ANG II stimulation of NAD(P)H oxidases leads to the formation of superoxide anion (O(2)-*, which, in turn, activates ADPR cyclase. Afferent arterioles were isolated from rat kidney wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
65
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 51 publications
4
65
0
Order By: Relevance
“…Inhibition of CD38 with NA, or inhibition of the cADPR and NAADP pathways, in the presence of the NOX inhibitors or ROS scavenger did not further suppress AICR. These observations are consistent with reports in renal afferent arterioles and cardiac myocytes that Ang II stimulates NOX to generate ROS, leading to enhanced ADP-ribosyl cyclase activity (36,44).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Inhibition of CD38 with NA, or inhibition of the cADPR and NAADP pathways, in the presence of the NOX inhibitors or ROS scavenger did not further suppress AICR. These observations are consistent with reports in renal afferent arterioles and cardiac myocytes that Ang II stimulates NOX to generate ROS, leading to enhanced ADP-ribosyl cyclase activity (36,44).…”
Section: Discussionsupporting
confidence: 93%
“…This result suggests that the contribution of CD38 to the physiological functions of various vasculatures may be different. Vascular functions of CD38 have not been examined in cerebral arteries despite the abundance of expression, but they are well characterized in renal arteries and arterioles (10,11,14,34,36). It has been shown that CD38-dependent pathways modulate cytosolic [Ca 21 ] i and contractile functions in renal afferent arteries and arterioles and can account for 50% of the contractile response to Ang II, ET-1, and norepinephrine (10).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, sphingosine is not involved in the renal vasoconstriction stimulated by either ANG II or nSMase. However, it has been reported that OEA causes vasorelaxation partly via an endothelium-dependent mechanism (14). More recently, attention has turned to a possible role of COX metabolites in the OEA actions in the vasculature (49).…”
Section: Discussionmentioning
confidence: 99%
“…In cases in which NO production is significantly decreased and/or reactive oxygen species (ROS) levels are increased, the activation of RhoA/Rho-kinase may contribute to increased vascular tone (29,30,52). Furthermore, Src-dependent pathways and nicotinic acid adenine dinucleotide phosphate (NAADP), another second messenger generated by the enzyme ADP-ribosyl (ADPR) cyclase, may contribute to the Ca 2ϩ signaling of ANG II (8,13,14,29,30). Furthermore, to support the hypothesis that the ANG II/AT 1 receptor/nSMase/ceramide-PLA 2 /TxA 2 pathway contributes to the regulation of renal vasoconstriction, we demonstrated the expression of nSMase, ceramide, and cPLA 2 in the smooth muscle layer of intrarenal vessels.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, ANG II-induced hypertrophy is inhibited by over-expression of CAT, or by inhibition of vascular NAD(P)H oxidase [41,42]. It is well established that ROS are important intracellular messengers of many physiological and pathological effects of circulating ANG II, since they are blocked by apocynin, a NAD(P)H oxidase inhibitor [43] or by CAT over-expression [28,41]. In addition, ANG II has been shown to stimulate the increase of both monocyte chemotactic protein 1 (MCP-1) and vascular cell adhesion protein 1 (VCAM-1) mRNA expression in rat aorta.…”
Section: Cerebellar Angiotensin II and Reactive Oxigen Speciesmentioning
confidence: 99%